2018
DOI: 10.7717/peerj.4998
|View full text |Cite
|
Sign up to set email alerts
|

Vertical stratification of plant–pollinator interactions in a temperate grassland

Abstract: Visitation of plants by different pollinators depends on individual plant traits, spatial context, and other factors. A neglected aspect of small-scale variation of plant–pollinator interactions is the role of vertical position of flowers. We conducted a series of experiments to study vertical stratification of plant–pollinator interactions in a dry grassland. We observed flower visitors on cut inflorescences of Centaurea scabiosa and Inula salicina placed at different heights above ground in two types of surr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…As discussed above, plants grown with high amount of water were taller and produced more flowers and these characteristics had a positive effect on the visitation of individual plants as reported in other plant species ( e.g. , Mitchell et al, 2004 ; Akter, Biella & Klecka, 2017 ; Klecka, Hadrava & Koloušková, 2018a ). However, other modifications of plant traits induced by water stress also apparently decreased the visitation of plants grown with low amount of water, because the effect of water availability on the number of flower visitors per plant persisted even after accounting for differences in the number of open flowers and plant height in our analysis.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…As discussed above, plants grown with high amount of water were taller and produced more flowers and these characteristics had a positive effect on the visitation of individual plants as reported in other plant species ( e.g. , Mitchell et al, 2004 ; Akter, Biella & Klecka, 2017 ; Klecka, Hadrava & Koloušková, 2018a ). However, other modifications of plant traits induced by water stress also apparently decreased the visitation of plants grown with low amount of water, because the effect of water availability on the number of flower visitors per plant persisted even after accounting for differences in the number of open flowers and plant height in our analysis.…”
Section: Discussionsupporting
confidence: 52%
“…Flower visitation rate of insect-pollinated plants depends on visual cues indicating high floral reward such as the number of open flowers ( Conner & Rush, 1996 ; Akter, Biella & Klecka, 2017 ) and the size of floral display ( Grindeland, Sletvold & Ims, 2005 ; Parachnowitsch & Kessler, 2010 ; Biella et al, 2019 ), and on the amount and quality of nectar and pollen ( Cresswell, 1999 ; Grindeland, Sletvold & Ims, 2005 ). Other morphological features can also influence plant detection by potential pollinators, such as plant height ( Junker et al, 2013 ; Klecka, Hadrava & Koloušková, 2018a ; Hernández-Villa et al, 2020 ), local plant clustering ( Elliott & Irwin, 2009 ; Akter, Biella & Klecka, 2017 ), and flower colour ( Reverté et al, 2016 ). Measurements of flower visitation with plants grown in the spring 2017 and plants grown in the summer 2018 revealed that in both cases plants grown with higher amount of water had a significantly higher number of flower visitors compared to plants grown under low amount of water irrespective of nitrogen supply.…”
Section: Discussionmentioning
confidence: 99%
“…For example, pollen of Centaurea stoebe and Dianthus deltoides was common in the samples from C. chalybea but almost absent in samples from the other two Ceratina species, where it was replaced by pollen of Sedum rupestre , Allium flavum , and other plants. Such pattern of resource partitioning could be caused by different preferences for floral traits ( Junker et al, 2013 ; Klecka et al, 2018a ), variation in preferred plant height ( Klecka, Hadrava & Koloušková, 2018b ), or by interspecific competition ( Schoener, 1974 ; Palmer, Stanton & Young, 2003 ), as demonstrated previously in bumblebees ( Inouye, 1978 ; Graham & Jones, 1996 ).…”
Section: Discussionmentioning
confidence: 77%
“…Flower number, plant height and flower size are also likely to be correlated with the overall resource status of individual plants (Hodgins & Barrett, 2008;Weiner, 1988). Many studies have demonstrated that fruit and seed production could increase with increasing flower number, plant height or mean flower size of individual plants (Andersson, 1991;de Jong, Waser, Price, & Ring, 1992;Klecka, Hadrava, & Koloušková, 2018;Mitchell, 1994;Ohara & Higashi, 1994;Ruane, Rotzin, & Congleton, 2014).…”
Section: Introductionmentioning
confidence: 99%